2011
DOI: 10.1080/13632469.2011.555057
|View full text |Cite
|
Sign up to set email alerts
|

Shaking Table Tests of the Smart Restorable Sliding Base Isolation System (SRSBIS)

Abstract: This article reports on the experimental investigation of the Smart Restorable Sliding Base Isolation System (SRSBIS), proposed for the earthquake-resistant design of structures. SRSBIS is composed of steel-PTFE Flat Sliding Bearings (FSBs), supporting gravity loads while allowing large horizontal displacements, and superelastic Shape Memory Alloy (SMA) wires, providing the necessary horizontal stiffness and restoring capability. Three different configurations can be alternatively considered based on the arran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…A modern base isolation system composed of steel-teflon flat sliding bearings was proposed by Jalali et al [5]; they used SMA truss elements to provide a proper restoring capability. Besides, Cardone et al [6] conducted an experimental investigation of the Smart Restorable Sliding Base Isolation System (SRSBIS) using superelastic Shape Memory Alloy (SMA) wires, and the outcomes revealed that the SRSBIS can be reliably used in passive control of structures. Dolce et al [7] evaluated the effectiveness of SMA braces in reinforced concrete structures, results from shaking table test demonstrated that SMA bars can provide favorable self-centering capability.…”
Section: Introductionmentioning
confidence: 98%
“…A modern base isolation system composed of steel-teflon flat sliding bearings was proposed by Jalali et al [5]; they used SMA truss elements to provide a proper restoring capability. Besides, Cardone et al [6] conducted an experimental investigation of the Smart Restorable Sliding Base Isolation System (SRSBIS) using superelastic Shape Memory Alloy (SMA) wires, and the outcomes revealed that the SRSBIS can be reliably used in passive control of structures. Dolce et al [7] evaluated the effectiveness of SMA braces in reinforced concrete structures, results from shaking table test demonstrated that SMA bars can provide favorable self-centering capability.…”
Section: Introductionmentioning
confidence: 98%
“…For example, the SMA-cable-restrained high-damping rubber bearing developed by Fang et al [43] has been first adopted in Datianba #2 bridge constructed in Yunnan Province, China, effectively demonstrating the real-world application of SMA for seismic protection of civil infrastructure. In view of the effectiveness of incorporating the SMA with different isolators for response mitigation [14,[42][43][44][45][46][47][48][49][50][51][52], the advantages of the SMA, i.e., superelastic re-centering and energy dissipation, show the promising prospect of application in structural seismic resilience enhancement [33,43]. Particularly, several superelastic seismic isolators, e.g., superelastic flat sliding bearing [47][48][49][50][51][52] and superelastic friction pendulum [14,[53][54][55][56][57], in which the friction-based isolators are incorporated with the SMA wires/ cables, have been investigated and seismic performances have been analytically and experimentally demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…In view of the effectiveness of incorporating the SMA with different isolators for response mitigation [14,[42][43][44][45][46][47][48][49][50][51][52], the advantages of the SMA, i.e., superelastic re-centering and energy dissipation, show the promising prospect of application in structural seismic resilience enhancement [33,43]. Particularly, several superelastic seismic isolators, e.g., superelastic flat sliding bearing [47][48][49][50][51][52] and superelastic friction pendulum [14,[53][54][55][56][57], in which the friction-based isolators are incorporated with the SMA wires/ cables, have been investigated and seismic performances have been analytically and experimentally demonstrated. e SMA utilized in the superelastic friction pendulum is to enhance the re-centering capacity [14,53].…”
Section: Introductionmentioning
confidence: 99%
“…[29][30][31][32] Several studies have revealed that combining the SMA device with isolators is particularly efficient for residual displacement mitigation. [33][34][35][36][37][38][39] Particularly, considering the advantages of the SMA as damping and re-centering components, several SMA-based isolators, which combine the superelastic SMA wire/cables with the traditional friction isolators, have been examined for performance improvement of structures, for example, the SMA-based pure-friction sliding bearing, [38][39][40][41][42][43][44] SMA-friction pendulum bearing, [45][46][47][48][49] which demonstrated the feasibility using the SMA device to enhance the structural seismic resilience. Note that when the pure-friction sliding bearing integrates with SMA, the lateral stiffness and re-centering capability are all dependent on the SMA device, [38][39][40] which means that the SMA device needs to be fabricated using much more amount of SMA wires than the SMA-friction pendulum bearing.…”
Section: Introductionmentioning
confidence: 99%
“…[33][34][35][36][37][38][39] Particularly, considering the advantages of the SMA as damping and re-centering components, several SMA-based isolators, which combine the superelastic SMA wire/cables with the traditional friction isolators, have been examined for performance improvement of structures, for example, the SMA-based pure-friction sliding bearing, [38][39][40][41][42][43][44] SMA-friction pendulum bearing, [45][46][47][48][49] which demonstrated the feasibility using the SMA device to enhance the structural seismic resilience. Note that when the pure-friction sliding bearing integrates with SMA, the lateral stiffness and re-centering capability are all dependent on the SMA device, [38][39][40] which means that the SMA device needs to be fabricated using much more amount of SMA wires than the SMA-friction pendulum bearing. This is because the SMA used in SMA-friction pendulum bearing is mainly employed to enhance the re-centering performance.…”
Section: Introductionmentioning
confidence: 99%